Invisible Thin‐Film Patterns with Strong Infrared Emission as an Optical Security Feature. Issue 21 (2nd September 2018) - Bakan, Gokhan; Ayas, Sencer; Serhatlioglu, Murat; Elbuken, Caglar; Dana, Aykutlu
Abstract: Spectrally selective thermal emission is in high demand for thermophotovoltaics, radiative cooling, and infrared sensing applications. Spectral control of the emissivity is historically achieved by choosing the material with suitable infrared properties. The recent advancements in nanofabrication techniques that lead to enhanced light–matter interactions enable optical properties like infrared emissivity that are not naturally available. In this study, thermal emitters based on nanometer‐thick dielectrics on field‐enhancement surfaces as optical security features are proposed. Such a function is achieved by generating patterns by ultrathin dielectrics that are transparent in the visible and exhibit strong infrared absorption in the spectral range of thermal cameras. The invisible patterns are then revealed by thermal imaging. The field‐enhancement surfaces enhance the emissivity of the patterns, in turn reduce the minimum temperature to detect the thermal emission down to ≈30 °C from >150 °C to exploit ubiquitous heat sources like the human body. The study provides a framework for the use of thermal emitters as optical security features and demonstrates applications on rigid and flexible substrates. Abstract : Nanometer‐thick SiO2 patterns are encrypted in the visible wavelength regime to be decrypted in the infrared. This study provides a framework for the use of thermal emitters as optical security features and demonstrates applications on rigid and flexible substrates.